Chronic LCMV Infection Is Fortified with Versatile Tactics to Suppress Host T Cell Immunity and Establish Viral Persistence - Caleb J. Studstill; Bumsuk Hahm (Viruses, 2021)
Ever since the immune regulatory strains of lymphocytic choriomeningitis virus (LCMV), such as Clone 13, were isolated, LCMV infection of mice has served as a valuable model for the mechanistic study of viral immune suppression and virus persistence. The exhaustion of virus-specific T cells was demonstrated during LCMV infection, and the underlying mechanisms have been extensively investigated using LCMV infection in mouse models. In particular, the mechanism for gradual CD8+ T cell exhaustion at molecular and transcriptional levels has been investigated. These studies revealed crucial roles for inhibitory receptors, surface markers, regulatory cytokines, and transcription factors, including PD-1, PSGL-1, CXCR5, and TOX in the regulation of T cells. However, the action mode for CD4+ T cell suppression is largely unknown. Recently, sphingosine kinase 2 was proven to specifically repress CD4+ T cell proliferation and lead to LCMV persistence. As CD4+ T cell regulation was also known to be important for viral persistence, research to uncover the mechanism for CD4+ T cell repression could help us better understand how viruses launch and prolong their persistence. This review summarizes discoveries derived from the study of LCMV in regard to the mechanisms for T cell suppression and approaches for the termination of viral persistence with special emphasis on CD8+ T cells.